Cosmid based mutagenesis causes genetic instability in Streptomyces coelicolor, as shown by targeting of the lipoprotein signal peptidase gene - Munnoch, John T. (Sci Rep, 2016)
Bacterial lipoproteins are extracellular proteins tethered to cell membranes by covalently attached lipids. Deleting the lipoprotein signal peptidase (lsp) gene in Streptomyces coelicolor results in growth and developmental defects that cannot be restored by reintroducing lsp. This led us to hypothesise that lsp is essential and that the lsp mutant we isolated previously had acquired compensatory secondary mutations. Here we report resequencing of the genomes of wild-type M145 and the cis-complemented ∆lsp mutant (BJT1004) to map and identify these secondary mutations but we show that they do not increase the efficiency of disrupting lsp and are not lsp suppressors. We provide evidence that they are induced by introducing the cosmid St4A10∆lsp, as part of ReDirect PCR mutagenesis protocol, which transiently duplicates a number of important cell division genes. Disruption of lsp using a suicide vector (which does not result in gene duplication) still results in growth and developmental delays and we conclude that loss of Lsp function results in developmental defects due to the loss of all lipoproteins from the cell membrane. Significantly, our results also indicate the use of cosmid libraries for the genetic manipulation of bacteria can lead to phenotypes not necessarily linked to the gene(s) of interest.